BUNDENGAN: SOCIAL MEDIA AS A SPACE FOR COLLABORATION IN THE CONSERVATION AND REVIVAL OF AN ENDANGERED MUSICAL INSTRUMENT - Rosie H Cook; Luqmanul Chakim; Sa’id Abdulloh; Nicole Tse1; Margaret Kartomi (Proceeding IICACS, 2019)
The widespread use of social media in cultural heritage and conservation projects principally makes use of its capacity for public-facing engagement and the promotion of cultural institutions and events. Its potential as an inclusive, accessible and dynamic research output is less well-established. This paper focuses upon the potential of social media as a complementary form of conservation documentation, in response to the use of interdisciplinary and cross-cultural collaboration between source communities and collecting institutions as a means to preserve both material and intangible cultural heritage. Using the conservation of a rare and endangered musical instrument called bundengan as a case study, this paper will assess the uses of social media platforms in both documenting and enabling collaboration between the source community in Wonosobo, Java, Indonesia, and academic researchers based in Indonesia and Australia.